Indexical and statistical approaches to investigate the integrated origins of elements in the sediment of Teesta River, Bangladesh: sediment quality and ecological risk assessment. Issue 4 (10th March 2023) - Khan, Rahat; Hossain, Shabiha; Anik, Amit Hasan; Phoungthong, Khamphe; Islam, Abu Reza Md. Towfiqul; Saha, Narottam; Idris, Abubakr M.; Alam, Mahbub
Abstract : This study investigates ecological consequences from the combined provenance (natural and manmade) of fifteen metal(oid)s (Na, Al, K, Ti, Cr, Mn, Co, Zn, As, Rb, Sb, Cs, Ba, Th, and U) from a major Indo-Bangla transboundary river (Teesta). Abstract : This study investigates ecological consequences from the combined provenance (natural and manmade) of fifteen metal(oid)s (Na, Al, K, Ti, Cr, Mn, Co, Zn, As, Rb, Sb, Cs, Ba, Th, and U) from a major Indo-Bangla transboundary river (Teesta). Instrumental neutron activation analysis has been performed to calculate the elemental concentration for a total of thirty sediment samples which accumulated from the upper, middle and downstream section of the Teesta River. In comparison with the crustal origin Rb, Th, and U were 1.5–2.8 times elevated. Elements from upstream and midstream sediments showed greater spatial variability than those from downstream sediments in terms of Na, Rb, Sb, Th, and U. Statistical approaches suggested the dominance of geogenic sources (Na, K, Al, Ti, Co, and Ba) of elements over anthropogenic sources (Cr and Zn). Alkali feldspar and aluminosilicates release lithophilic minerals into the sediments under the redox condition (U/Th = 0.18). Site-specific ecotoxicological indices advocated that some specific locations are highly hazardous relative to Cr and Zn. From SQG-based guidelines, Cr showed higher potential toxicity in some upstream locations relative to Zn, Mn, and As. In order to attain the knowledge limitation of northern transboundary rivers from Bangladesh, this study of origin and relative environmental impact will be beneficial for policy makers.